2021
DOI: 10.3389/fmicb.2021.644979
|View full text |Cite
|
Sign up to set email alerts
|

Taxonomy and Phylogeny of the Fomitopsis pinicola Complex With Descriptions of Six New Species From East Asia

Abstract: Fomitopsis pinicola is a common brown-rot fungal species found in northern hemisphere. It grows on many different gymnosperm and angiosperm trees. Recent studies show that it is a species complex; three species from North America and one species from Europe have been recognized in this complex. In the current study, six new species in the Fomitopsis pinicola complex were discovered from East Asia, based on morphological characters and phylogenetic analyses inferred from the sequence data of the internal transc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 36 publications
(33 citation statements)
references
References 36 publications
1
32
0
Order By: Relevance
“…Cui & Shun Liu formed separate lineages, respectively ( Figure 1 ). In addition, the current phylogenetic analyses also showed that Fomitopsis and other related brown-rot fungal genera clustered together within the antrodia clade, which are consistent with previous studies ( Ortiz-Santana et al, 2013 ; Han et al, 2016 ; Liu et al, 2019 , 2021a ; Zhou et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…Cui & Shun Liu formed separate lineages, respectively ( Figure 1 ). In addition, the current phylogenetic analyses also showed that Fomitopsis and other related brown-rot fungal genera clustered together within the antrodia clade, which are consistent with previous studies ( Ortiz-Santana et al, 2013 ; Han et al, 2016 ; Liu et al, 2019 , 2021a ; Zhou et al, 2021 ).…”
Section: Discussionsupporting
confidence: 92%
“…Subsequently, phylogenetic analyses indicated that Fomitopsis is polyphyletic and the taxonomic position of Fomitopsis is still problematic ( Kim et al, 2005 , 2007 ; Justo and Hibbett, 2011 ; Ortiz-Santana et al, 2013 ). Recently, taxonomic and phylogenetic studies on Fomitopsis have been carried out and several new species have been described ( Li et al, 2013 ; Han et al, 2014 , 2016 ; Han and Cui, 2015 ; Soares et al, 2017 ; Haight et al, 2019 ; Liu et al, 2019 , 2021a ; Zhou et al, 2021 ). Han et al (2016) investigated phylogenetic relationships of Fomitopsis and its related genera and reported that species previously placed in Fomitopsis were divided into seven lineages: Fomitopsis s. s., Fragifomes B.K.…”
Section: Introductionmentioning
confidence: 99%
“…The phylogeny of Oligoporus, combined 7-gene (ITS, nLSU, nuSSU, mtSSU, RPB1, RPB2, TEF1) dataset, included sequences from 43 fungal samples representing 21 taxa. They were downloaded from GenBank and generated in the present study ( Liu et al (2021) were variable and parsimony-uninformative and 1516 were parsimony informative. Maximum parsimony analysis yielded four equally-parsimonious trees (TL = 3925, CI = 0.600, RI = 0.784, RC = 0.471, HI = 0.400) and a strict consensus tree of these trees is shown in Fig.…”
Section: Molecular Phylogenymentioning
confidence: 99%
“…Soares & Gibertoni was proposed as a new combination ( Soares et al 2017 ; Tibpromma et al 2017 ; Liu et al 2019 ). In the latest study, ten species have been recognised in the Fomitopsis pinicola complex ( Haight et al 2019 ; Liu et al 2021 ). So far, 25 species have been accepted in Fomitopsis sensu stricto (s.…”
Section: Introductionmentioning
confidence: 99%
“…The PCR cycling schedules for different DNA sequences used in this study followed those used in Zhou et al and Liu et al [23,24] with some modifications. The PCR procedure for ITS, mt-SSU, and TEF1 was as follows: initial denaturation at 95 • C for 3 min, followed by 35 cycles at 94 • C for 40 s, 54 • C for 45 s, and 72 • C for 1 min, and a final extension of 72 • C for 10 min.…”
Section: Dna Extraction and Sequencingmentioning
confidence: 99%